POSSIBLE REASONS OF RESISTANCE IN LARVAE OF ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜§ð˜³ð˜¶ð˜¨ð˜ªð˜±ð˜¦ð˜³ð˜¥ð˜¢ (ABBOT & SMITH, 1797) INFECTED BY ð˜‰ð˜¢ð˜¤ð˜ªð˜ð˜ð˜¶ð˜´ ð˜µð˜©ð˜³ð˜¶ð˜³ð˜ªð˜¯ð˜¨ð˜ªð˜¦ð˜¯ð˜´ð˜ªð˜´ var. ð˜¬ð˜¶ð˜³ð˜´ð˜µð˜¢ð˜¬ð˜ª - Garcia, M. A.; SimÃµes, M.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2020)
POSSIBLE REASONS OF RESISTANCE IN LARVAE OF ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜§ð˜³ð˜¶ð˜¨ð˜ªð˜±ð˜¦ð˜³ð˜¥ð˜¢ (ABBOT & SMITH, 1797) INFECTED BY ð˜‰ð˜¢ð˜¤ð˜ªð˜ð˜ð˜¶ð˜´ ð˜µð˜©ð˜³ð˜¶ð˜³ð˜ªð˜¯ð˜¨ð˜ªð˜¦ð˜¯ð˜´ð˜ªð˜´ var. ð˜¬ð˜¶ð˜³ð˜´ð˜µð˜¢ð˜¬ð˜ª